Teacher Strategies for Strengthening Learning Motivation in Islamic Religious Education: An Exploratory Case Study in an Indonesian Public Senior High School - Fesa Nurpika; Ismail Fahri; M. Thontawi (Women, Education, and Social Welfare, 2026)
Learning motivation is central to inclusive student support because it shapes whether learners attend to, participate in, and persist with classroom activity. This exploratory qualitative case study examines documented preliminary observations of Islamic Religious Education (IRE) instruction in Grade X E8 at an Indonesian public senior high school. The evidence concerns one IRE teacher and a class of 34 students. The analysis identifies a heterogeneous motivation profile: some students were attentive and participatory, whereas others were less focused, hesitant to respond, or minimally involved. Teacher practices comprised aperception, communication of learning objectives, motivational prompts, everyday-life examples, lectures, question-and-answer, and discussion. The findings are synthesized as a Motivational Alignment Cycle linking value framing, participation architecture, relational reinforcement, and responsive observation. The contribution is a context-sensitive framework that explains why method variation alone may not be sufficient unless students also perceive relevance, psychological safety, and attainable opportunities to contribute. The study informs teacher professional development and school-level psychosocial support in IRE and comparable value-oriented subjects. Because the source evidence is preliminary and does not include completed interviews, transcripts, or outcome measures, the article makes no causal or generalizable effectiveness claims.